Energy-Related Uncertainty and Crypto-Currency Environmental Attention: Time-Varying Perspective - Kuchkarov, Takhir; Mamadiyarov, Zokir; Khakimov, Ziyodulla; Sabirova, Oysuluv; Matmurodov, Khojimurod; Raimboyeva, Mashkhura; Umarova, Sarvinoz (International Journal of Energy Economics and Policy, 2025)
The article investigates the time-varying effects of cryptocurrency environmental attention on energy-related uncertainty, distinguishing itself from previous research that focuses on static relationships or disregards the time-varying nature of these interactions in the context of global financial and geopolitical events. A time-varying parameter vector autoregression (TVP-VAR) model is estimated based on global monthly data from February 2014 to October 2022. Geopolitical risk and financial stress are also utilized as control variables. The findings demonstrate that cryptocurrency environmental attention significantly negatively affects energy-related uncertainty in 2019. Additionally, financial stress exhibits a negative response to shocks in cryptocurrency environmental attention during the years 2015 and 2016. Geopolitical risk demonstrates a positive correlation with cryptocurrency environmental attention in 2021, with these relationships showing considerable variation across distinct time periods and global events. This article presents important information for policymakers regarding the regulation of cryptocurrency and energy markets. The results indicate that monitoring environmental factors in cryptocurrency markets may reduce energy-related uncertainties during stable conditions; however, this influence weakens in the face of global crises, including pandemics or geopolitical tensions.